2014
DOI: 10.1155/2014/427318
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Alzheimer’s Disease: Why Did Antioxidant Therapy Fail?

Abstract: Alzheimer's disease (AD) is the most common form of dementia in the elderly, with increasing prevalence and no disease-modifying treatment available yet. A remarkable amount of data supports the hypothesis that oxidative stress is an early and important pathogenic operator in AD. However, all clinical studies conducted to date did not prove a clear beneficial effect of antioxidant treatment in AD patients. In the current work, we review the current knowledge about oxidative stress in AD pathogeny and we sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
207
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(221 citation statements)
references
References 112 publications
0
207
0
1
Order By: Relevance
“…Does 'redox' provide a platform for therapeutic intervention? Although preclinical data suggest that treatment with free radical quenchers can improve ER-stress-dependent atrophy (Back et al, 2009;Malhotra et al, 2008), the translation of such therapies into the clinic is challenging (see, for example, Persson et al, 2014). One of the associated problems is illustrated by the dual role that NRF2 has in cancer; by increasing the endogenous antioxidant capacities, NRF2-inducing treatments lower the sensitivity to carcinogens but, at the same time, increase the risk of resistance against anti-cancer chemotherapy (Ma, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Does 'redox' provide a platform for therapeutic intervention? Although preclinical data suggest that treatment with free radical quenchers can improve ER-stress-dependent atrophy (Back et al, 2009;Malhotra et al, 2008), the translation of such therapies into the clinic is challenging (see, for example, Persson et al, 2014). One of the associated problems is illustrated by the dual role that NRF2 has in cancer; by increasing the endogenous antioxidant capacities, NRF2-inducing treatments lower the sensitivity to carcinogens but, at the same time, increase the risk of resistance against anti-cancer chemotherapy (Ma, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study confirmed the beneficial effect of Se on neurotoxicity induced by aluminium chloride (AlCl 3 ). Lakshmi et al showed that this micronutrition effectively prevented the harmful effects of this toxin in behaviour and biochemical changes, and a decrease in brain oxidative damages, neuronal inflammation and improvement of the working and attention memory were observed [134].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Increased amounts of 4-hydroxy-2-nonenal (4-HNE) and malondialdehyde which are products of lipid peroxidation [18] have been found on post-mortem analysis of human brains from aceruloplasminemia patients [19]. Protein carbonyl groups and 8-oxo-7,8-dihydro-2-deoxyguanosine (8-oxdG) as markers of oxidative damage to proteins and DNA can be detected in tissue of various neurodegenerative disorders including AD [20][21][22][23]. Also, depletion of endogenous antioxidants such as glutathione has been documented in the substantia nigra of PD patients further supporting the role of oxidative stress in neurodegeneration [24].…”
Section: Causes and Consequences Of Cerebral Iron Accumulationmentioning
confidence: 99%